Daily Moderate Exercise Is Beneficial and Social Stress Is Detrimental to Disease Pathology in Murine Lupus Nephritis - Aqel, Saba I.; Hampton, Jeffrey M.; Bruss, Michael; Jones, Kendra T.; Valiente, Giancarlo R.; Wu, Lai-Chu; Young, Matthew C.; Willis, William L.; Ardoin, Stacy; Agarwal, Sudha; Bolon, Brad; Powell, Nicole; et al. (Frontiers in Physiology, 2017)
Daily moderate exercise (DME) and stress management are underemphasized in the care of patients with lupus nephritis (LN) due to a poor comprehensive understanding of their potential roles in controlling the inflammatory response. To investigate these effects on murine LN, disease progression was monitored with either DME or social disruption stress (SDR) induction in NZM2410/J mice, which spontaneously develop severe, early-onset LN. SDR of previously established social hierarchies was performed daily for six days and DME consisted of treadmill walking (8.5 m/min for 45 min/day). SDR significantly enhanced kidney disease when compared to age-matched, randomly selected control counterparts, as measured by histopathological analysis of H&E staining and immunohistochemistry for complement component 3 (C3) and IgG complex deposition. Conversely, while 88% of non-exercised mice displayed significant renal damage by 43 weeks of age, this was reduced to 45% with exercise. DME also reduced histopathology in kidney tissue and significantly decreased deposits of C3 and IgG complexes. Further examination of renal infiltrates revealed a macrophage-mediated inflammatory response that was significantly induced with SDR and suppressed with DME, which also correlated with expression of inflammatory mediators. Specifically, SDR induced IL-6, TNF-α, IL-1β, and MCP-1, while DME suppressed IL-6, TNF-α, IL-10, CXCL1, and anti-dsDNA autoantibodies. These data demonstrate that psychological stressors and DME have significant, but opposing effects on the chronic inflammation associated with LN; thus identifying and characterizing stress reduction and a daily regimen of physical activity as potential adjunct therapies to complement pharmacological intervention in the management of autoimmune disorders, including LN.